Narrar la derrota: el testimonio revolucionario a partir del nuevo milenio (El Hilo de la Fabula, 2021)
At the turn of the millennium, the stories of triumph, characteristic of the first decades of the Cuban Revolution - those of the new man and the heroic life stories - had ultimately lost their validity and power of conviction. Instead, disenchantment and a general sense of detachment from the previous forms of constructing reality, as well as a simultaneous openness and a search for new ways of narrating memory and history dominated. These new sensibilities are also embraced by Casa de las Américas, when rethinking the modalities of the testimonial genre, institutionalized by the Cuban cultural institution along with the creation of a literary award in this category in 1970. In this article, two Casa de las América  testimonial award winning texts are analyzed: Mañana es lejos (memorias verdes de los años rabiosos) (2009) by Eduardo Rosenzvaig and Su paso (2011) by Carlos E. Bishoff, in order to look into the ways of writing testimony after  2000.
Keywords: Testimony; Autofiction; Disenchantment; Memory; Casa de las Américas